The elevated serum levels of calcineurin and nuclear factor of activated T-cells 1 in children with Kawasaki disease - Yameng Sun; Jingjing Liu; Zhimin Geng; Yijing Tao; Fenglei Zheng; Ying Wang; Songling Fu; Wei Wang; Chunhong Xie; Yiying Zhang; Fangqi Gong (BMC, 2020)
Abstract Background The calcineurin and nuclear factor of activated T-cells (CaN-NFAT) signaling pathway had been found to be associated with Kawasaki disease (KD) susceptibility and coronary artery aneurysm formation as a contributor. To evaluate serum calcineurin (CaN) and nuclear factor of activated T-cells 1(NFAT1) levels in patients with Kawasaki disease (KD). Methods Serum levels of CaN and NFAT1 were measured by enzyme-linked immunosorbent assay method in 66 healthy children and 74 KD patients at acute, afebrile and subacute stage. Results The serum levels of CaN and NFAT1 increased significantly in the acute stage, and decreased progressively in the afebrile and subacute stage, along with the reduction of C-reactive protein, white blood cells and neutrophil counts. And in the acute stage, the afebrile stage and the subacute stage, the expression of CaN and NFAT1 was upregulated significantly in KD patients compared to that in the healthy control. After the IVIG treatment, the serum levels of CaN and NFAT1 declined significantly in IVIG responders. However, the CaN and NTAT1 levels in the IVIG non-responders declined slowly. And in the afebrile stage, the NFAT1 levels were lower in KD patients with coronary artery lesions (CALs) (268.82 ± 11.96 ng/ml) than those without CALs (285.84 ± 25.13 ng/ml). However, the serum levels of CaN in KD patients with CALs had no significant difference with those in KD patients without CALs. Conclusions The specific regulation of CaN and NFAT1 serum levels in the course of KD was suggested that both of them were related in the development of KD.